DGM-TOP: automatic identification of the critical boundaries in atrial tachycardia - Van Den Abeele, Robin; Hendrickx, Sander; Carlier, Niels; Wülfers, Eike M.; Santos Bezerra, Arthur; Verstraeten, Bjorn; Lootens, Sebastiaan; Desplenter, Karel; Okenov, Arstanbek; Nezlobinsky, Timur; Haas, Annika; Luik, Armin; et al. (Frontiers in Physiology, 2025)
IntroductionIn the latest research on topology in cardiac arrhythmia, it was demonstrated through a fundamental mathematical principle called the index theorem that reentry based atrial tachycardias (AT) are maintained by pairs of counter-rotating waves that are either complete or near-complete rotations. Each wave is centered around a different anatomical object that exhibits a non-zero index/topological charge, called a critical boundary. Interconnecting both critical boundaries with an ablation line terminates the tachycardia.MethodsThis research focuses on the specific algorithms for calculating the index/topological charge of each anatomical boundary, called DGM-TOP. The algorithm used analyzes the electroanatomical map of the patient, extracting the nodes at each boundary. The index is then calculated for each boundary by sequentially summing the differences in local activation time and normalizing by the cycle length. Boundaries with a non-zero index are identified as critical boundaries.Results and discussionUsing this method, pairs of critical boundaries were consistently detected in 100% of the 578 in silico and 100% of the 24 clinical ATs. Adhering to the previously described index theorem. Additionally, ablation results in both datasets show that termination of AT is only possible by interconnecting both critical boundaries. This outcome highlights the importance of detecting the critical boundaries before deciding on the correct ablation line, as any ablation line that does not connect both critical boundaries is unable to terminate the AT. Moreover, in the case of incorrect ablation, the BCL-algorithm was proposed to estimate the increase in tachycardia cycle length. However, only moderate correlation (r2=0.62) is observed for simulations, indicating a refinement of this BCL-algorithm is necessary in addition to a larger clinical dataset.